Pengaruh Rasio Padat/Cair dan Waktu Pengadukan pada Proses Ekstraksi Silika dari Palm Oil Fly Ash (POFA) - Fika Rahma Yuni; Lita Darmayanti; Dewi Fitria (Al-Ard: Jurnal Teknik Lingkungan, 2021)
Palm oil fly ash (POFA) is one of the solid wastes produced from burning palm kernel shells and coir as a steam generator for palm oil mills. POFA has a high silica content and might potentially to be used as an adsorbent. The removal of impurity metals and the separation of SiO2 by extraction process is a way to improve the performance of silica. The extraction process is influenced by several factors including the solid/liquid ratio and the stirring time. This study used a solid/liquid ratio of 1: 8, 1:10, 1:12 and a stirring time of 120; 150; 180; and 210 minutes. The results showed the highest mass of silica deposits was at a ratio of 1:12 and stirring time of 210 minutes with a mass of 18.35 grams or 73.4% of 25 grams of POFA with a silica content of 47.97% and a silica surface area 8.18 m2/g. Silica from each variation was tested on peat water. The highest removal efficiency of color, organic matter, and Fe were 80%, 46%, and 37% respectively by the extracted silica with a solid/liquid ratio 1:12 and stirring time 210 minutes.